A Dynamics and Inconsistency of Justice Collaborators in Corruption Cases in Indonesia - Sri Endah Indriawati (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study aims to analyze the dynamics and inconsistency of the treatment of Justice Collaborators (JCs) in corruption cases in Indonesia. Justice Collaborators play a crucial role in uncovering corruption cases; however, the regulations governing their protection and rewards remain unclear, creating legal uncertainty. Against this background, the study focuses on the legal issues related to the protection and rewards for JCs, as well as the challenges encountered in their application, particularly in organized corruption cases. This research employs a normative legal approach, examining existing laws, regulations, and relevant literature to analyze the inconsistencies and disparities in the treatment of JCs. The findings indicate that the lack of clarity regarding the definition of "main perpetrators" and the absence of harmonization between legal frameworks hinder the effective protection of JCs. Furthermore, the inconsistency in judicial decisions leads to uncertainty about the rights and rewards for those cooperating with law enforcement. The study suggests the need for clearer regulations and greater harmonization among law enforcement agencies to ensure optimal protection for JCs in uncovering corruption cases.